The Temporal Courses of Phonological and Orthographic Encoding in Handwritten Production in Chinese: An ERP Study - Zhang, Qingfang; Wang, Cheng (Frontiers in Human Neuroscience, 2016)
A central issue in written production concerns how phonological codes influence the output of orthographic codes. We used a picture-word interference paradigm combined with the event-related potential technique to investigate the temporal courses of phonological and orthographic activation and their interplay in Chinese writing. Distractors were orthographically related, phonologically related, orthographically plus phonologically related, or unrelated to picture names. The behavioral results replicated the classic facilitation effect for all three types of relatedness. The ERP results indicated an orthographic effect in the time window of 370 to 500 ms (onset latency: 370 ms), a phonological effect in the time window of 460 to 500 ms (onset latency: 464 ms), and an additive pattern of both effects in both time windows, thus indicating that orthographic codes were accessed earlier than, and independent of, phonological codes in written production. The orthographic activation originates from the semantic system, whereas the phonological effect results from the activation spreading from the orthographic lexicon to the phonological lexicon. These findings substantially strengthen the existing evidence that shows that access to orthographic codes is not mediated by phonological information, and they provide important support for the orthographic autonomy hypothesis.